PERAN PT. PEGADAIAN (PERSERO) DALAM PENYIDIKAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Muhammad, Budi (UNES Law Review, 2019)
Articles 111 to 126 of Law No. 35 of 2009 concerning Narcotics, determine the difference in criminality for narcotics abuse based on the severity of the evidence of abused narcotics. For this purpose the investigator must weigh the evidence by working with PT. Pawnshop. This research specification is Descriptive Analysis. The role of PT. Pegadaian (Persero) Padang in Narcotics Criminal Investigation is in the case of proof of narcotics crime in the activity of weighing the weight of evidence of drugs, must attach a request for weighing evidence of drug evidence and after completion of the weighing, a Minutes must be signed signed by both parties and witnessed by witness investigators or auxiliary investigators and suspects. Constraints include the lack of sophisticated tools that can be used accurately in weighing evidence of narcotics. On PT. Pegadaian holidays it is not open, while the detention process must be continued, and based on legal certainty, the law enforcement process must be quickly carried out. Lack of Human Resources at PT Pegadaian who is expert in weighing.